The Essential-Oil-Bearing Rose Collection Variability Study in Terms of Biochemical Parameters - Viktor Zolotilov; Natalya Nevkrytaya; Olga Zolotilova; Sevilia Seitadzhieva; Elena Myagkikh; Vladimir Pashtetskiy; Mikhail Karpukhin (Agronomy, 2022)
The primary task when breeding new varieties of essential-oil-bearing rose is to increase the essential oil content and quality. The purpose of the present research is to study the essential-oil-bearing rose collection variability in terms of the essential oil content and component composition and to identify opportunities for isolating the specimens promising for selection. The study of a collection of 112 specimens was carried out in 2017–2020 in the context of the piedmont of Crimea. The decanted essential oil content was determined using the hydrodistillation method. The component composition of rose essential oil was analyzed by gas chromatography on Crystal 5000.2. The essential oil components were identified by comparing their Kovats retention indices to the literature values. A high variability in the essential oil content in the collection (Cv = 36.3% at the average, over 4 years) and the major components content in the essential oil (Cv = 22.1–45.9%) was found. In the context of the piedmont of Crimea, the major components’ percentage content in essential oil from all the specimens including the five Bulgarian varieties did not meet the GOST ISO 9842-2017 standard requirements. This is indicative of a high-degree sensitivity to the soil and weather conditions in the region. It was found that the citronellol, geraniol, and nerol content in essential oil dropped significantly in extreme high temperature and drought conditions. Seven specimens rich in essential oil contained in the raw plant material (0.030–0.049%) and thirteen specimens with a high yield of concrete (0.31–0.39%) were identified and have been recommended for inclusion in the breeding process.